2011
DOI: 10.1111/j.1365-2702.2011.03772.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in nursing practice: associations with responses to and coping with errors

Abstract: These findings highlight the role of senior staff in the establishment of a supportive, trustful ward climate, so that nurses can learn from errors, prevent their recurrence and improve patient safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
1
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 28 publications
2
54
1
5
Order By: Relevance
“…There are several factors that can influence the reliability of an instrument, for example, the number of items, size of the sample and the tendency to value some items over others. (13) Cronbach's alpha values obtained in other studies that used the Ways of Coping Questionnaire by Folkman and Lazarus had values slightly above those found in this study: from 0.66 to 0.81 among nurses working in a hospital, (19) and 0.49 to 0.72 among spouses of patients undergoing coronary artery bypass surgery. (13) Men used the strategy confrontation more often in comparison to women (p = 0.018).…”
Section: Discussionmentioning
confidence: 61%
“…There are several factors that can influence the reliability of an instrument, for example, the number of items, size of the sample and the tendency to value some items over others. (13) Cronbach's alpha values obtained in other studies that used the Ways of Coping Questionnaire by Folkman and Lazarus had values slightly above those found in this study: from 0.66 to 0.81 among nurses working in a hospital, (19) and 0.49 to 0.72 among spouses of patients undergoing coronary artery bypass surgery. (13) Men used the strategy confrontation more often in comparison to women (p = 0.018).…”
Section: Discussionmentioning
confidence: 61%
“…; Karga et al. ). Feeling inadequate, they re‐evaluate the circumstances, experience self‐doubt, and lose confidence (Harrison et al.…”
Section: Resultsmentioning
confidence: 97%
“…; Karga et al. ). Despite this, avoidance strategies were not necessarily ineffective as a retrospective study by Harrison et al.…”
Section: Resultsmentioning
confidence: 97%
“…Kagan and Barnoy () stated that the patient safety culture of an institution is positively and distinctively related to the rate of medical error reporting and that a proper patient safety culture would prepare personnel to report errors. Karga, Kiekkas, Aretha, and Lemonidou () suggested that accepting responsibility for errors and receiving social support are important predictors of positive changes within a nonblaming culture. In a study carried out on this topic (Bodur & Filiz, ; Hellings, Schrooten, Klazinga, & Vleugels, ), it was determined that there is a punitive culture, and this prevents reporting errors and reducing healthcare errors.…”
Section: Discussionmentioning
confidence: 99%